Efeitos do herbicida clethodim (Poquer®) nas interações alelopáticas entre as linhagens produtoras de toxinas de Microcystis aeruginosa e Raphidiopsis raciborskii: o papel da variação de nitrogênio - Alves, Fernanda Breda (2019)
Cyanobacteria are photosynthetic organisms that make up the base of the aquatic food chain. Changes in the physical and chemical conditions of aquatic environments, such as increased nutrients and the presence of agrochemicals, alter the structure and dynamics of phytoplankton. Herbicides contaminate the aquatic environment through surface runoff at high concentrations; these compounds cause oxidative stress, interfere with the normal functioning of enzymes and alter the metabolic profile of microalgae and cyanobacteria. The present study investigated the toxicological and physiological effects of clethodim herbicide, as well as nitrogen variation in allelopathic interactions and toxin production by Microcystis aeruginosa BCCUSP232 and Raphidiopsis raciborskii ITEPA1. Effective concentrations (EC50) after 96 hours of exposure of both strains to clethodim were 192.98 mg / L and 168.73 mg / L for R. raciborskii and M. aeruginosa, respectively. The presence of clethodim significantly increased the total microcystin content of M. aeruginosa. In mixed cultivation M. aeruginosa, presented higher cell density when exposed to clethodim, while the highest density of R. raciborskii was observed when exposed to clethodim with limited nitrogen addition. The total content of microcystins (MCs) in mixed culture was 68% higher in nitrogen-enriched cultures than control. A similar increase in MC content was recorded in M. aeruginosa monocultures treated with R. raciborskii exudate. Total saxitoxin concentration was higher in R. raciborskii mixed cultures simultaneously exposed to high nitrogen and clethodim. The intracellular H2O2 content of M. aeruginosa cultures decreased while in R. raciborskii cultures increased during exposure to nitrogen and clethodim. GST activities in cultures of both strains were higher in the presence of clethodim. Our study revealed that nitrogen enrichment and low clethodim concentration could lead to excessive proliferation of M. aeruginosa and R. raciborskii and cyanotoxin production in aquatic environments